Assessment of probabilistic seismic performance of RC columns jacketed by FRP winding wires using analytical models. (15th September 2018) - Choi, Eunsoo; Jeon, Jong-Su; Lee, Jong-Han; Park, Sun Hee; Ha, Seungwoo
Highlights: Two nonlinear analytical models of RC columns are developed in OPENSEES. Experimental results of RC columns retrofitted by FRP wire jackets are used. Two models are compared from a practical point of view. Seismic fragility curves of RC columns are generated using the two models. Abstract: This study assessed the seismic vulnerability of reinforced concrete columns jacketed by fiber-reinforced polymer (FRP) wires. To achieve this goal, four column specimens subjected to cyclic load tests were selected to validate the analytical model of existing and FRP retrofitted columns in OpenSees; the specimens included two existing columns with lap-spliced and continuous longitudinal reinforcement and two FRP wire-jacketed columns with lap-spliced and continuous longitudinal reinforcement. Two types of material models ('Concrete' versus 'Pinching') were used to simulate the concrete material models of columns. Based on the validation results, the advantages and disadvantages of using of two material models were considered. Additionally, to compare the seismic performance of the columns subjected to ground motions, their fragility curves were developed. Comparison results revealed that the retrofitting effect using the 'Pinching' model is superior, but use of the 'Concrete' model is also acceptable. However, the 'Pinching' model is more vulnerable than the 'Concrete' model for specimens exhibiting limited ductility.